The intestinal γδ T cells: functions in the gut and in the distant organs - Li, Guo-Qing; Xia, Jiliang; Zeng, Weihong; Luo, Weijia; Liu, Logen; Zeng, Xi; Cao, Deliang (Frontiers in Immunology, 2023)
Located in the frontline against the largest population of microbiota, the intestinal mucosa of mammals has evolved to become an effective immune system. γδ T cells, a unique T cell subpopulation, are rare in circulation blood and lymphoid tissues, but rich in the intestinal mucosa, particularly in the epithelium. Via rapid production of cytokines and growth factors, intestinal γδ T cells are key contributors to epithelial homeostasis and immune surveillance of infection. Intriguingly, recent studies have revealed that the intestinal γδ T cells may play novel exciting functions ranging from epithelial plasticity and remodeling in response to carbohydrate diets to the recovery of ischemic stroke. In this review article, we update regulatory molecules newly defined in lymphopoiesis of the intestinal γδ T cells and their novel functions locally in the intestinal mucosa, such as epithelial remodeling, and distantly in pathological setting, e.g., ischemic brain injury repair, psychosocial stress responses, and fracture repair. The challenges and potential revenues in intestinal γδ T cell studies are discussed.